Poétiques sur le pas de porte : de la magopinaciophilie comme terrain littéraire - Ninon Chavoz (Continents manuscrits, 2019)
The present article reflects on a very narrow fieldwork: by focusing on a mailbox overwhelmed by the promotional flyers edited by Parisian marabouts, I intend to investigate the abundant literary follow-ups of frequently dismissed textual objects. Those flyers, which have been collected and indexed on-line since 2005, allow for an intercultural connection between Africa and Europe as well as for the circulation of poetical fragments. Although marabouts distinctively appears in works by Sami Tchak, Calixthe Beyala, Olivier Cadiot and Patrick Grainville, there presence remains discrete and isolated and they are to this day overshadowed by the prominent literary figure embodied by the “sapeur”.